Vesicular-arbuscular mycorrhizae in coffee seedlings in the southern region of Minas Gerais state, Brazil - Siqueira, José Oswaldo; Colozzi-Filho, Arnaldo; Oliveira, Elizabeth de; Fernandes, Adauto B.; Florence, Moema L. (Pesquisa Agropecuaria Brasileira, 2014)
A survey was conducted to assess the mycorrhizal status of coffee (Coffea arabica L) seedlings produced in the southern part of Minas Gerais State, Brazil. The survey showed that most seedlings were poorly colonized and had a very low spore density in the rhizosphere. From the 72 samples studied, 79% had colonization percentages below 20% with a mean of 13.8%, and 65% of the 72 had less than 20 spores/100 ml of substrate with a mean of 16.3. Ten species of VAM fungi were found with Acaulospora scrobiculata, A. morrowae and A. spinosa being the most common. Correlation analyses between soil and plant variables and fungal root colonization and spore density were of little value in explaining variations in mycorrhizal development. However, natural low infectivity of the substrate and the systematic use of pesticides and fertilizers are suggested as factors responsible for the low mycorrhizal development and spore density in the rhizosphere of these seedlings. Implications of the poor mycorrhizal development to seedling growth are discussed.